Global Sea Ice Coverage from Satellite Data: Annual Cycle and 35-Yr Trends - Parkinson, Claire L. (Journal of climate, 2014)
Well-established satellite-derived Arctic and Antarctic sea ice extents are combined to create the global picture of sea ice extents and their changes over the 35-yr period 1979–2013. Results yield a global annual sea ice cycle more in line with the high-amplitude Antarctic annual cycle than the lower-amplitude Arctic annual cycle but trends more in line with the high-magnitude negative Arctic trends than the lower-magnitude positive Antarctic trends. Globally, monthly sea ice extent reaches a minimumin February and a maximum generally in October or November. All 12 months show negative trends over the 35-yr period, with the largest magnitude monthly trend being the September trend, at −68 200 ± 10 500 km² yr−1(−2.62% ± 0.40% decade−1), and the yearly average trend being −35 000 ± 5900 km² yr−1(−1.47% ± 0.25% decade−1).